Transformation of the security sector in Malawi - 1994 to 2014 - Chirwa, Misheck Colyns (My University, 2016)
The study was carried out to determine the transformation of the security institutions and related management bodies in Malawi from 1994 to 2014 as the country shifted from authoritarian rule to democratic governance. Transformation of the security sector (TSS) is the process by which a country in transitional democracy formulates or re-orients the policies, structures and capacities of security institutions, and private security groups in the security sector. Such tasks in a newly democratic Malawi required new sets of values among political leaders, the legislature, security practitioners as well as the civil society. TSS is sometimes expressed as Security Sector Reform (SSR), Security Sector Governance (SSG) and as well as Security and Justice Sector Reform (SJSR) (African Union 2010). The study employed qualitative method as the mainstay and partly some statistical data interpretation was employed using a Statistical Package for Social Sciences (SPSS) software for the purpose of data visualisation and to identify information in graphical presentation. Forty participants were involved from security institutions and management bodies (army, police intelligence, prisons services), residing in Lilongwe, the Capital City of Malawi. iii The findings reveal that the security sector and management bodies in Malawi failed to transform/perform sufficiently. The opportunity for reform was significant however it was limited because the transition to democracy stalled due to continued abuse of power by the elected authorities. This may have been a deliberate attempt by those in power in order to maintain a weak security sector and management bodies for own interests. The current structure of the security sector in Malawi may be weak for the following reasons: Lack of expertise by the elected authorities, lack of overall security reviews every year, non-existent of various security policies, lack of modern equipment and technology and last but not least, mean budgetary consideration and very low salaries to the security members. Furthermore, the basic security legislation should be reformed because Malawi inherited a legal structure from the colonial rule that requires modification. The results from this study suggest that the transition process calls for a comprehensive TSS/SSR or SSG of the entire security sector and management bodies. The government should reinforce policy action across security institutions whereby the elected authorities, legislature, security practitioners and civil societies are involved in locally owned TSS. An important fact is positive change in the level of responsiveness by the State to the rights, views and demands of its citizens.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy March 2015
Keywords: Security sector--Malawi; Malawi--Politics and government--21st century